2007
DOI: 10.1097/01.hjh.0000254376.80864.d3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between early and delayed systemic treatment with candesartan of rats after ischaemic stroke

Abstract: The present study demonstrates that only an early but not a delayed onset of treatment with candesartan exerts neuroprotection after focal ischaemia. The degree of neurological impairments did not correlate with the infarct volume, which was reduced only after the low dose of candesartan. The high dose of candesartan failed to reduce the infarct volume, probably because of an excessive blood pressure decrease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 46 publications
5
26
0
Order By: Relevance
“…Gohlke et al 21 have shown earlier that oral administration of 0.1 mg kg À1 candesartan inhibited the central response to angiotensin II. This finding is in agreement with other studies showing that postischemic low-dose, but not moderate-or high-dose, administration of candesartan is neuroprotective against transient focal ischemia in both normotensive 5 and hypertensive rats. 6 Furthermore, our results show that lowering the BP shortly after reperfusion in SHR results in a decline in cerebral blood flow in the affected cortex, which could overshadow any potential beneficial Candesartan 10 mg kg À1 12 37.6 ± 0.3 38.0 ± 0.5 37.9 ± 0.5 38.0 ± 0.4 37.9 ± 0.4…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Gohlke et al 21 have shown earlier that oral administration of 0.1 mg kg À1 candesartan inhibited the central response to angiotensin II. This finding is in agreement with other studies showing that postischemic low-dose, but not moderate-or high-dose, administration of candesartan is neuroprotective against transient focal ischemia in both normotensive 5 and hypertensive rats. 6 Furthermore, our results show that lowering the BP shortly after reperfusion in SHR results in a decline in cerebral blood flow in the affected cortex, which could overshadow any potential beneficial Candesartan 10 mg kg À1 12 37.6 ± 0.3 38.0 ± 0.5 37.9 ± 0.5 38.0 ± 0.4 37.9 ± 0.4…”
Section: Discussionsupporting
confidence: 83%
“…1 In experimental animal stroke models, recent studies have shown that postischemic administration of an angiotensin II type 1 receptor (AT 1 ) blocker (ARB) after transient middle cerebral artery (MCA) occlusion improves neurological outcomes and reduces infarct size. [2][3][4][5] However, it remains unclear whether the beneficial effects of ARBs are dose dependent. Several studies have suggested that high doses of ARBs are not beneficial because they cause hypotension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, early administration of candesartan (3 h after onset of ischemia) to normotensive rats has been shown to be neuroprotective, but only when excessive BP lowering is avoided (Brdon et al, 2007). We are the first group to add the additional benefit of a reduction in vascular damage and hemorrhage to the benefits of candesartan in SHRs as well as identifying an interaction between preexisting hypertension and stroke in the response to BP lowering with candesartan.…”
Section: Discussionmentioning
confidence: 99%
“…9 We have previously suggested that antihypertensive medications that increase angiotensin II levels such as thiazide diuretics, calcium antagonists, and ARBs could be more cerebroprotective than agents that lower angiotensin II levels such as ␤-blockers and angiotensin-converting enzyme inhibitors. 10 This hypothesis was based on experimental findings 11,12 but also was supported by a recent meta-analysis of 206 632 patients in 26 prospective randomized clinical trials. 13 Angiotensin II-decreasing drugs proved to be less stroke protective than antihypertensive drugs that increased angiotensin II levels.…”
Section: Article P 2969mentioning
confidence: 87%